2012
DOI: 10.1074/jbc.m111.334375
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Induces MUC5AC Protein Expression through the Activation of Sp1

Abstract: Background: Cigarette smokers have increased mucus secretion and MUC5AC gene expression. Results: Cigarette smoke increases Sp1 protein expression and activates Sp1 binding to a smoke-responsive promoter region of the MUC5AC. Conclusion: Sp1 is the key regulator of cigarette smoke-induced MUC5AC mRNA transcription in lung epithelial cells. Significance: Sp1 may be a putative target to treat mucus hypersecretion in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…Although WCS has been frequently used to model smoking-related lung disease (24,29) and the reduced CFTR function observed here is consistent with prior studies (2,9,24,29), the experiments conducted rely on acute CSE and are unlikely to capture the complexity of the airway environment in patients with COPD, such as airway inflammation, disrupted proteolytic balance, and ER stress (3,31,47,48). Although the conclusion that CFTR activation by roflumilast contributes to therapeutic benefit in patients with chronic bronchitis is supported by specificity controls, as an efficacious activator of intracellular cAMP, roflumilast may also improve the function of surface epithelia via other pathways.…”
Section: Original Researchsupporting
confidence: 79%
See 1 more Smart Citation
“…Although WCS has been frequently used to model smoking-related lung disease (24,29) and the reduced CFTR function observed here is consistent with prior studies (2,9,24,29), the experiments conducted rely on acute CSE and are unlikely to capture the complexity of the airway environment in patients with COPD, such as airway inflammation, disrupted proteolytic balance, and ER stress (3,31,47,48). Although the conclusion that CFTR activation by roflumilast contributes to therapeutic benefit in patients with chronic bronchitis is supported by specificity controls, as an efficacious activator of intracellular cAMP, roflumilast may also improve the function of surface epithelia via other pathways.…”
Section: Original Researchsupporting
confidence: 79%
“…The degree of CFTR inhibition by WCS was sufficient to reduce ASL depth, which is known to decrease the efficiency of MCT (30). Because the severity of the ion transport and ASL abnormalities was intermediate compared with the defect observed in CF epithelial cells, it seems likely that this decrement is sufficient to initiate a cascade of mucus retention and infection in vivo, particularly if present over multiple years and combined with enhanced mucus expression also caused by cigarette smoking (2,31).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that MUC5B, but not MUC5AC, is essential for mucociliary clearance activity and the prevention of bacterial spread from the nasal cavity to the lower respiratory tract (312). Mucus secretion and mucociliary clearance are enhanced in the presence of inflammatory mediators (313) and microbial pathogens (314)(315)(316) and following exposure to cigarette smoke (317). Antimicrobial substances, including enzymes (lysozyme), protease inhibitors (secretory leukoprotease inhibitor, elastase inhibitor, ␣1-antiprotease, and antichymotrypsin), antimicrobial peptides (␤-defensins and L37), and oxidants (nitric oxide and hydrogen peroxide), are secreted by epithelial cells into the airway surface liquid and provide a further line of defense against microbes (318).…”
Section: Protecting the Cns From Microbial Invasion Via The Nasal Cavitymentioning
confidence: 99%
“…Di 48 ) and 0.05 mg pCMV-b-galactosidase (b-gal) (Clontech) using Effectene (Qiagen). The TGF-b1 promoter-luciferase plasmid was also used as a template to construct new plasmids with deletion of the SREBP-1 or the Sp1 binding site using overlapping primer pairs.…”
Section: Luciferase Assaymentioning
confidence: 99%